Evaluasi Pengelolaan Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan - Rahayu, Hastanti Agustin; Halim, Abdul (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2016)
The legalization of the law No. 28 Year 2009 on Regional Taxes and Levies is one of changes in fiscal policy that is quite fundamental to the implementation of regional autonomy, including the regionalization of Land and Building Tax. The implementations such as the Yogyakarta Regional Regulation No. 2 of 2011 on Land and Building Tax effectedthe very significant consequences of changes, especially on the revenue management and the administration ofLand and Building Tax. This study aims to describe the management of Land and Building Tax (PBB P2) in Yogyakarta government, by using Friedman’s four quadrants analysis and ratio analysis. The result of this study is the effectiveness of the PBB P2 management in DPDPK Yogyakarta by 137.87% with very effectiveeffectiveness criteria. PBB P2 management efficiency in the first year was 2.99% with highly efficiency criteria. PBB P2revenue contribution gains 3.81% of theYogyakarta government’s local revenue in 2012. It’s “only” 0.28% with thevery low contribution criteria.PBB P2management in DPDPK Yogyakarta is based on Friedman’s four-quadrant approach in quadrant IV which is a quality quadrant of the impact. This shows a good management of tax collection againsts the potentials of PBB P2. The obstacles of PBB P2 management in DPDPK Yogyakarta include: there is no SOP of PBB P2management, assessment for NJOP reclassification, the Mayor’s regulations for NJOP, and updates of the database. Keywords: Land and Building Tax, Friedman’s four-quadrant analysis, ratio analysis.